2019
DOI: 10.1039/c9cp04700j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum optoelectronic properties in vertically stacked MoS2/h-BN/WSe2 van der Waals heterostructures

Abstract: Inserting an insulator at the interface in vdW heterostructure solar cell unit can improve the photoelectric conversion efficiency, and the insulator has an optimal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…[ 329 ] Further, researchers have used different thicknesses of h‐BN as a spacer to control the excitonic emission in TMDs such as bilayer MoS2, MoS 2 /WSe 2, etc. [ 322,323 ] In both cases it has been observed that the lifetime of interlayer excitons has significantly improved due to delay in the recombination of e–h pairs. Thus, h‐BN plays an important role in separating the e‐ and h‐ in different layers of TMDs; very useful in high‐efficiency solar cells.…”
Section: Doping Vdw Heterostructures and Nanocompositesmentioning
confidence: 99%
“…[ 329 ] Further, researchers have used different thicknesses of h‐BN as a spacer to control the excitonic emission in TMDs such as bilayer MoS2, MoS 2 /WSe 2, etc. [ 322,323 ] In both cases it has been observed that the lifetime of interlayer excitons has significantly improved due to delay in the recombination of e–h pairs. Thus, h‐BN plays an important role in separating the e‐ and h‐ in different layers of TMDs; very useful in high‐efficiency solar cells.…”
Section: Doping Vdw Heterostructures and Nanocompositesmentioning
confidence: 99%
“…Interestingly, Tan et al theoretically proposed that charge recombination can be suppressed by inserting a 2–3 nm thick hBN insulating layer between the MoS 2 and WSe 2 and that the photoelectric conversion efficiency (PCE) of MoS 2 /hBN/WSe 2 photovoltaic devices can be approximately doubled. They theoretically predicted that the PCE exceeding 23% could be obtained by increasing the TMDC thickness and optimizing the hBN thickness [ 178 ].
Figure 11.
…”
Section: Applications Of 25d Materialsmentioning
confidence: 99%
“…[13][14][15] Understanding the mechanism of photo carries relaxation in vdW HSs is a crucial step in the development of potential applications since it determines the response speed and efficiency of photo-electron conversion. [16,17] Ultrafast optical spectroscopy is an ideal technique for unveiling all of the mysterious processes. [18,19] In the past few years, a variety of studies have been carried out on photocarriers' relaxation in 2D vdW HSs.…”
mentioning
confidence: 99%